BIG BOOK: STUDENTS’ PERCEPTION OF ITS BENEFITS TO READING SKILL - Cahyani, Chandrika Rahmania; Megawati, Fika (Premise: Journal of English Education and Applied Linguistics, 2024)
This research uncovers students' perceptions of the benefits of significant books on reading skills. A purposive descriptive case study was used to explore their perceptions of the benefits of big books on reading skills and the challenges in practicing the activity. Five elementary school students who read big books became participants in this research. To fill the gap, this research aimed to describe the benefits of big books on students' reading activities. An open-ended questionnaire was used for data collection. Data were collected through structured interviews and analyzed using Interpretative Phenomenological Analysis (IPA). The results showed that students positively perceived reading using big books. They argued that this technique stimulated and encouraged their creativity. However, it was found that big book has limited verbal representation and development of other skills. This research implies that big books can enhance creativity, are easy to use, and are not fixated on technology.